(3′R)-hydroxytabernaelegantine C: A bisindole alkaloid with potent apoptosis inducing activity in colon (HCT116, SW620) and liver (HepG2) cancer cells. (24th December 2016) - Paterna, Angela; Gomes, Sofia E.; Borralho, Pedro M.; Mulhovo, Silva; Rodrigues, Cecília M.P.; Ferreira, Maria-José U.
Abstract: Ethnopharmacological relevance: Tabernaemontana elegans Stapf. (Apocynaceae) is a medicinal plant traditionally used in African countries to treat cancer. Aims of the study: To discover new apoptosis inducing lead compounds from T. elegans and provide scientific validation of the ethnopharmacological use of this plant. Materials and methods: Through fractionation, (3′ R )-hydroxytaberanelegantine C (1 ), a vobasinyl-iboga bisindole alkaloid, was isolated from a cytotoxic alkaloid fraction of the methanol extract of T. elegans roots. Its structure was identified by spectroscopic methods, mainly 1D and 2D NMR experiments. Compound1 was evaluated for its ability to induce apoptosis in HCT116 and SW620 colon and HepG2 liver carcinoma cells. The cell viability of compound1 was evaluated by the MTS and lactate dehydrogenase (LDH) assays. Induction of apoptosis was analyzed through Guava ViaCount assay, by flow cytometry, caspase-3/7 activity assays and evaluation of nuclear morphology by Hoechst staining. To determine the molecular pathways elicited by1 exposure, immunoblot analysis was also performed. Results: (3′ R )-hydroxytaberanelegantine C (1 ) displayed strong apoptosis induction activity as compared to 5-fluorouracil (5-FU), the most used anticancer agent in colorectal cancer treatment. In the MTS assay, compound1 exhibited IC50 values similar or lower than 5-FU in the three cell lines tested. The IC50 value of1 was also calculated in CCD18co normal human colon fibroblasts. The lactate dehydrogenase assay showed increased LDH release by compound1, and the Guava ViaCount assay revealed that1 significantly increased the incidence of apoptosis to a further extent than 5-FU. Moreover, the induction of apoptosis was corroborated by evaluation of nuclear morphology by Hoechst staining and caspase-3/7 activity assays of1 treated cells. As expected, in immunoblot analysis, compound1 treatment led to poly(ADP-ribose) polymerase cleavage. This was accompanied by decreased anti-apoptotic proteins Bcl-2 and XIAP steady state levels in all three cancer cell lines tested. Conclusions: Compound1 showed remarkable induction of apoptosis in HCT116, SW620 and HepG2 cells. Together, the results suggest that compound1 is a promising lead structure for inducing apoptosis. Graphical abstract: